2020
DOI: 10.1155/2020/8819749
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Palm Oil-Fried Street Kokor on Liver and Kidney Biomarkers of Swiss Albino Mice

Abstract: Background. Foods fried with oils at streets contain many harmful substances for health. Locally fried foods are consumed commonly in our society, yet their health effect is not studied. Objective. To assess the effect of palm oil-fried street kokor on liver and kidney biomarkers of Swiss Albino mice. Methods. Thirty-two male and female Swiss Albino mice with the age of 10-12 weeks old were divided randomly into four groups of eight members with equal male and female subgroups. The control group (group I) rece… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 27 publications
4
7
0
Order By: Relevance
“…On the other hand, the low serum creatinine concentration observed in the groups of animals after consumption of palm olein enriched with plant extracts would be related to the low oxidative status of these oil samples. These results corroborate those of Amsalu et al (2020) and Chew et al (2019). Indeed, Amsalu, Wondimnew, Mateos, Fekadie & Bogale, (2020) showed that serum creatinine increased in rats following the consumption of fried palm oil, whereas the investigations of Chew et al (2019) showed that the simultaneous consumption of citrus leaf extracts and thermoxidized palm olein resulted in a decrease in serum creatinine in rats.…”
Section: Effect Of the Different Oil Samples On Liver And Kidney Para...supporting
confidence: 92%
See 1 more Smart Citation
“…On the other hand, the low serum creatinine concentration observed in the groups of animals after consumption of palm olein enriched with plant extracts would be related to the low oxidative status of these oil samples. These results corroborate those of Amsalu et al (2020) and Chew et al (2019). Indeed, Amsalu, Wondimnew, Mateos, Fekadie & Bogale, (2020) showed that serum creatinine increased in rats following the consumption of fried palm oil, whereas the investigations of Chew et al (2019) showed that the simultaneous consumption of citrus leaf extracts and thermoxidized palm olein resulted in a decrease in serum creatinine in rats.…”
Section: Effect Of the Different Oil Samples On Liver And Kidney Para...supporting
confidence: 92%
“…These results corroborate those of Amsalu et al (2020) and Chew et al (2019). Indeed, Amsalu, Wondimnew, Mateos, Fekadie & Bogale, (2020) showed that serum creatinine increased in rats following the consumption of fried palm oil, whereas the investigations of Chew et al (2019) showed that the simultaneous consumption of citrus leaf extracts and thermoxidized palm olein resulted in a decrease in serum creatinine in rats.…”
Section: Effect Of the Different Oil Samples On Liver And Kidney Para...supporting
confidence: 92%
“…The concentrations of ALT and AST in the serum are correlated with the extent of liver tissue damage [17,18]. Conversely, the reoccurrence of the aminotransferases' activities in the serum close to the normal levels indicates the hepatocytes regeneration and the recovery of the liver parenchyma [3,18,19]. Based on the results of the current study, there were indications of the liver damage in the group that received a high dose of the extract, as evident by the elevated serum AST and ALT levels.…”
Section: Serum Alt and Astsupporting
confidence: 47%
“…Urea and creatinine are the most frequently ordered blood analyses to assess the status of the kidney function. Urea is produced by protein breakdown and excreted in urine whereas creatinine is a non-protein nitrogenous compound that is produced by the breakdown of creatine in muscles and excreted by filtration through the kidney at a constant rate [18]. In the current study, the serum urea levels were elevated in the rat group that received the extract at a high dose.…”
Section: Serum Albumin Urea and Creatininementioning
confidence: 46%
See 1 more Smart Citation